Synthesis of Ti-Zr alloy by powder metallurgy - Slokar, Ljerka (Array, 2019)
Due to good properties, which meet the requirements for use as biomaterials, titanium and titanium alloys have been increasingly used as dental implants. Until recently, dental titanium alloys were produced by casting. Since this process does not meet the terms of economy and efficiency, the production of titanium implants by powder metallurgy are very promising. Therefore, in this work titanium alloy with addition of 10 at. % zirconium is prepared by powder metallurgy with the goal of obtaining the best producing conditions, which would result in the titanium alloy of the adequate properties for use as dental implants. High values of green densities were achieved even only by uniaxial pressing. Further, sintering temperature of 1673 K resulted in the alloy of the highest sintered density and microhardness. The results of this investigation revealed the processing parameters applicable for the production of titanium-zirconium dental implants by powder metallurgy.